VIBRATION CHARACTERISTIC ANALYSIS OF THE ROTOR SYSTEM OF SPHERICAL HYBRID SLIDING BEARING - ZHU Rui; SHEN Jingfeng; LU Mingming; GU Chunxing (Jixie qiangdu)
Under the medium and high speed of spherical hybrid sliding bearings, the dynamic pressure effect causes the fluid in the wedge space to whirl, and the vibration characteristics of the rotor may be affected by the oil whirl, so the rotation accuracy of the main shaft is reduced. The spherical hybrid sliding bearings with the orifice throttle was divided into cylindrical and conical whirl. The lubrication mathematical model and rotor dynamic model were established and solved simultaneously, the journal center trajectory and vibration amplitude were obtained. The influence of the centroid offset distance and initial deflection angle on the vibration characteristics of the rotor system were studied.The results show that, compared with the pure cylindrical whirl, the stability of the journal center trajectory decreases and the vibration amplitude increases after considering the conical whirl.With the increase of the centroid offset distance, the stability and vibration amplitude of the journal center trajectory decrease greatly.With the increase of the initial deflection angle, the stability and vibration amplitude of the journal center trajectory decrease only slightly.It can be concluded that changing the distance of the centroid offset has more influence on the stability of the journal center trajectory and the vibration characteristics of the rotor system than changing the initial deflection angle.